A Combination of Anti-PD-L1 Treatment and Therapeutic Vaccination Facilitates Improved Retroviral Clearance via Reactivation of Highly Exhausted T Cells - Torben Knuschke (American Society for Microbiology, 2021)
Despite significant efforts, vaccines are not yet available for every infectious pathogen, and the search for a protective approach to prevent the establishment of chronic infections, i.e., with HIV, continues. Immune checkpoint therapies targeting inhibitory receptors, such as PD-1, have shown impressive results against solid tumors.